STUDY OF PHYSICAL ACTIVITY AND DIETARY INTERVENTIONS FOR WEIGHT MANAGEMENT DURING PREGNANCY OF BULGARIAN WOMEN - Diana POPOVA‐DOBREVA (Editura Universitatii Transilvania din Brasov, 2018)
These The term 'weight management' includes: assessing and monitoring body weight; preventing someone from becoming overweight (body mass index [BMI] 25-29.9 kg/m²) or obese (BMI greater than or equal to 30 kg/m²); helping someone to achieve and maintain a healthy weight before, during and after pregnancy by eating healthily and being physically active and gradually losing weight after pregnancy (www.nice.org.uk). A survey was conducted with 717 Bulgarian women between 19 and 35 years of age.    The purpose of the study is to determine advice and support for weight control during pregnancy.  A section has been included at the end so that women can add any further comments they may have about their experience. Characteristic of women is made by age, BMI and occupation.  A discussion was held on the level of women's awareness and professional support.